Measurement of Myocardial Extracellular Volume Fraction by Using Equilibrium Contrast-enhanced CT: Validation against Histologic Findings - Bandula, Steve; White, Steven K.; Flett, Andrew S.; Lawrence, David; Pugliese, Francesca; Ashworth, Michael T.; Punwani, Shonit; Taylor, Stuart A.; Moon, James C. (Radiology, 2013)
To develop and validate equilibrium contrast material-enhanced computed tomography (CT) to measure myocardial extracellular volume (ECV) fraction by using a histologic reference standard and to compare equilibrium CT with equilibrium contrast-enhanced magnetic resonance (MR) imaging. A local ethics committee approved the study, and all subjects gave fully informed written consent. An equilibrium CT protocol was developed using iohexol at 300 mg of iodine per milliliter (bolus of 1 mg per kilogram of body weight administered at a rate of 3 mL/sec, followed immediately by an infusion of 1.88 mL/kg per hour with CT imaging before and at 25 minutes after injection of bolus of contrast agent) and ECV within the myocardial septum measured using both equilibrium CT and equilibrium MR imaging in patients with severe aortic stenosis. Biopsy samples of the myocardial septum collected during valve replacement surgery were used for histologic quantification of extracellular fibrosis with picrosirius red staining. Equilibrium CT- and equilibrium MR imaging-derived ECV measurements were compared with histologically quantified fibrosis by using Pearson correlation. Agreement between equilibrium CT and equilibrium MR imaging was assessed by using Bland-Altman comparison. Twenty-three patients (16 male, seven female; mean age, 70.8 years; standard deviation, 8.3) were recruited. The mean percentage of histologic fibrosis was 18% (intersubject range, 5%-40%). There was a significant correlation between both equilibrium CT- and equilibrium MR imaging-derived ECV and percentage of histologic fibrosis (r = 0.71 [P < .001] and r = 0.84 [P < .0001], respectively). Equilibrium CT-derived ECV was significantly correlated to equilibrium MR imaging-derived ECV (r = 0.73). ECV measured by using equilibrium CT in patients with aortic stenosis correlates with histologic quantification of myocardial fibrosis and with ECV derived by using equilibrium MR imaging.